Efektivitas Cylindrical Grip terhadap Kekuatan Otot Ekstremitas Atas pada Pasien Stroke - Tri Wahyuni Ismoyowati; Fransisca Winandari; Desty Irlani; Dewi Setia Rini; Yenny Dwiutami (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Stroke is a blockage of blood flow that results in reduced or no blood flow to the brain. Blockage of the middle cerebral artery causes muscle weakness and contralateral spasticity, as well as sensory deficits (hemianesthesia) due to damage to the precentral and postcentral lateral gyrus. Muscle weakness in stroke patients will affect muscle contraction, reduced muscle contraction is caused by reduced blood supply to the hindbrain and midbrain, so that it can inhibit the main pathways between the brain and spinal cord. This study is a literature review from several databases Pubmed, Google Scholar, NIH, NCBI, Research Gate, Microsoft Academia, Sience Direct and Proquest which aims to determine the effectiveness of Cylindrical Grip on upper extremity muscle strength in stroke patients.The search for articles is limited from 2011 to 2021. The author uses the keywords "Cylindrical Grip". The results of the study from eight databases obtained 106 articles then reduced by screening and obtained 5 relevant articles. After going through the study, it can be concluded that one of the symptoms in stroke is muscle weakness. One of the symptoms in stroke is muscle weakness or decreased muscle strength, muscle strength that occurs in stroke patients can be increased by several exercises, one of which is theExercise Range of Motion Cylindrical Grip. Cylindrical Grip is a functional hand exercise by grasping a cylindrical object, this movement will provide a modular sensory stimulus of fine touch and pressure on the end receptors of the organs that are responded to in the extremities. The existing stimulus will elicit a rapid response in the nerves to act on the stimulus, this mechanism is called feedback. This exercise can improve grip strength in the short term, and increase muscle strength in the long term. The results of this study can be considered for providing nursing interventions to increase muscle strength in stroke patients by providing exercises Range of Motion Cylindrical Grip.Keywords: cylindrical grip; stroke; muscle strengthABSTRAKStroke merupakan penyumbatan aliran darah yang mengakibatkan berkurang atau tidak mengalirnya darah ke otak. Penyumbatan pada arteri serebri media menyebabkan kelemahan otot dan spastisitas kontralaterla, serta defisit sensorik (hemianestesia) akibat kerusakan girus lateral presentralis dan postsentralis. Kelemahan otot pada pasien stroke akan mempengaruhi kontraksi otot, kontraksi otot yang berkurang disebabkan karena berkurangnya suplai darah ke otak belakang dan otak tengah, sehingga dapat menghambat hantaran jaras-jaras utama antara otak dan medula spinalis. Studi ini merupakan tinjauan literatur/literature review dari beberapa database Pubmed, Google Scholar, NIH, NCBI, Research Gate, Microsoft Academia, Sience Direct dan Proquest yang bertujuan untuk mengetahui efektivitas Cylindrical Grip terhadap kekuatan otot ekstremitas atas pada pasien stroke. Penelusuran artikel dibatasi dari tahun 2011 sampai dengan tahun 2021. Peneliti menggunakan kata kunci “Cylindrical Grip” dan “Stroke”. Hasil Studi literatur dari delapan database diperoleh 106 artikel kemudian diperkecil dengan screening dan diperoleh 5 artikel yang relevan. Setelah melalui penelaahan dapat disimpulkan bahwa salah satu gejala dalam stroke adalah kelemahan otot atau menurunnya kekuatan otot, kekuatan otot yang terjadi pada pasien stroke dapat ditingkat dengan beberapa latihan salah satunya dengan Latihan Range of Motion Cylindrical Grip. Cylindrical Grip adalah latihan fungsional tangan dengan cara menggenggam sebuah benda berbentuk silindris, gerakan ini akan memberi stimulus sensorik modular dari sentuhan halus dan tekanan pada reseptor akhir dari organ yang direspon di ekstremitas. Stimulus yang ada akan memunculkan respon yang cepat pada saraf untuk bertindak atas stimulus tersebut, mekanisme ini disebut umpan balik. Latihan ini dapat meningkatkan kekuatan genggaman dalam jangka pendek, dan meningkatkan kekuatan otot dalam waktu lama. Hasil studi ini dapat dipertimbangkan pemberian intervensi keperawatan untuk meningkatkan kekuatan otot pada pasien stroke dengan pemberian latihan Range of Motion Cylindrical GripKata kunci: cylindrical grip; stroke; kekuatan otot